2020
DOI: 10.21580/dms.2020.201.4806
|View full text |Cite
|
Sign up to set email alerts
|

Ibadah Mengolah Sampah Di Desa Grobog Wetan Kecamatan Pangkah Kabupaten Tegal

Abstract: <p><em>Having religion actually makes religious doctrine as an energy in solving the problems of humanity, one of them is the waste problem. The religious doctrine of the perfection of faith obtained by maintaining cleanliness must be realized by cooperating with multiple disciplines or other entities as an effort to create a clean and healthy society. The paradox of the society which is being busy with religious rituals, but neglecting the cleanliness of the environment continues until today, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Da'wah activities using environmental movements have also been disclosed by (Mubarok & Koidin, 2020). By focusing on foundation activities and the involvement of women and youth, the Mubarok and Koidin studies have shown the emergence of a paradigm of handling waste problems as worship.…”
Section: Literatur Reviewmentioning
confidence: 99%
“…Da'wah activities using environmental movements have also been disclosed by (Mubarok & Koidin, 2020). By focusing on foundation activities and the involvement of women and youth, the Mubarok and Koidin studies have shown the emergence of a paradigm of handling waste problems as worship.…”
Section: Literatur Reviewmentioning
confidence: 99%
“…Esmaeili (2019) added that poor waste management results in soil contamination, air pollution, respiratory and other health problems permanently. Seeing these conditions, the waste problem is a serious matter to be resolved (Mubarok & Koidin, 2020). Dai and Pakaya (2019) mentioned that the waste awareness movement by getting used to (culture) disposing of waste according to its place and sorting waste based on its category can be started by the community itself.…”
Section: Introductionmentioning
confidence: 99%